Analisis Konseling Sufistik dalam Buku Suluk KH. Ach. Hariri Abdul Adhim, Pilar Spiritualitas Ma’had Aly Salafiyah Syafi’iyah Situbondo - Ahmad Saifuddin Ma’sum; Abd. Mughni (Konseling At-Tawazun, 2023)
Each individual is required to be able to address and resolve various kinds of problems. However, only a few of the individuals realize that they also need counseling services. The[1]refore, the selection of the teachings of Sufism as an instrument approach is seen as appro[1]priate, because Sufistic thinking which focuses on cleaning the soul in order to get closer to Allah SWT is seen to be much in line with psychology which has been the basis of the coun[1]seling approach. This study aims to describe the values of Sufistic counseling in KH.’s Suluk Book. Ach. Hariri Abdul Adhim, Spirituality Pillar of Ma’had Aly Salafiyah Syafi’iyah Situ[1]bondo. The method used in this study is a qualitative method with the type of hermeneutical research, while the data analysis uses the objectivist hermeneutics cycle of the part-whole li[1]ne from Gadamer. The conclusion of this study is that there are 6 mystical counseling valu[1]es contained in KH. Ach. Hariri Abdul Adhim, Spirituality Pillars of Ma’had Aly Salafiyah Syafi’iyah Situbondo, namely: intelligence (irsyad), patience, purification of the heart, get[1]ting used to deliberations, dhikr, and prayer.